(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
The therapist contingent responding to clinically relevant behaviors (CRB) corresponds to Functional Analytic Psychotherapy (FAP) mechanism of change. The clinical procedures are summarized in five rules to therapists, which aim to maximize the frequency of CRBs. FAP logical interaction presents the five rules deployed in 12 steps, which describe therapist’s behaviors and their effects on client’s behaviors. Despite of the advances reached through refinement in FAP description and the empirical validation of FAP’ mechanism of change, the task of specifying therapist contingent responding is still unfinished. The purpose of this paper is to present FAP logical framework and discuss proposing an operationalization alternative to the therapist contingent responding to clinically relevant behaviors related to the clinical problem. The methods consisted in examining FAP logical framework steps to elucidate courses of actions for the therapist in response to the clinical problem. Four courses of action for the therapist are listed and illustrated with verbalizations extracted from recordings of client-therapist interactions. Possible undesirable effects caused by the discontinuing of reinforcement are discussed and questions for future studies are suggested.